Analiza povezanosti med spremenljikami ki doloeajo tekmovalno uspesnost v smuearskem teku - Pustovrh, J. (Kinesiologia Slovenica, 2005)
An analysis of some of the potential criteria of a competitive performance was made on a sample of young cross-country skiers aged between 13 and 14 years. The analysis covered all six races of the `Žito Cup` and three conventionally defined criteria of a competitive performance: FIS points, the POZ criterion (average time behind the winner in % in all races of the cup series) and the K-1 criterion. By applying Hotelling`s method of principal components and the Kaiser-Guttman criterion we extracted the first principal component (vector K-1) from six races of the Žito Cup, with which we succeeded in explaining 83% of the variance of young cross-country skiers` performances. In this case the fifth race contributed the least to the total subject of measurement. The results of the correlation analysis show a high correlation between individual conventionally defined criteria of a competitive performance (FIS, POZ and K-1). The correlations between the variables also show that the competitive performance of the measured subjects is not highly correlated with the cross-country skiing technique. Owing to the methodological advantages established, the application of the FIS-points variable was confirmed as a priority criterion of competition performance in both professional work in practice and in scientific research work.